Beyond Tobler's Hiking Function. Issue 4 (1st August 2020) - Goodchild, Michael F.
Abstract : Waldo Tobler introduced his hiking function in a little‐known article in 1993, as a formal representation of the relationship between topographic gradient and the velocity of an average hiker, with parameters estimated from some previously collected data. Such functions are becoming more useful as apps for route guidance proliferate. Numerous practical issues are raised by any effort to validate these functions empirically. Hiking functions in general allow routes to be measured on various criteria, including travel time, travel distance, or energy consumption, yet, few efforts have been made to calibrate similar functions for other modes of travel, other traveler profiles, and other route criteria. Connected and autonomous vehicles raise the possibility that route choice may take on greater significance in the context of system‐wide goals, rather than the current individual self‐interest.